Uma investigação dos impactos do PRONAF sobre as condições produtivas, econômicas e sociais dos agricultores familiares das regiões sul e nordeste, no período de 1996 a 2006 - Queiroz, Sabrina Faria de (2012)
The National Program for Strengthening Family Farming (PRONAF) was configured as a milestone in Brazilian rural areas by allowing differentiated access of family farmers to rural credit. That program was implemented in 1996 onwards with the objective to promote the sustainable development of family farming. However, only from 2000 the amount of credit hired was to show growth trend. For this reason this thesis is proposed to investigate and discuss the impact of PRONAF on some agricultural indicators in the South and Northeast regions from Brasil between the years 2000 and 2006. The basic hypothesis is that the PRONAF had positive effects and improved various agricultural indicators. To test this hypothesis, were built three variables of impact, which are: PRONFAB06, PRONFCDE06 AND PRONFINV06. These variables refer, respectively, to the resources of the PRONAF credit costing directed to family farmers more vulnerable in terms of income, to family farmers more capitalized and resources the PRONAF released for investment. With this, is through the use of spatial econometrics, we sought to assess whether the PRONAF, in three categories considered, exercised impacts on indicators of poverty, destitution, occupation, value added, land concentration and proportion of establishments with less than 50 and less than 10 hectares. The methodological procedures allowed the attesting the initial hypothesis. PRONAF succeeded, in general, reduce the levels of poverty and indigence and increase value added and employment in the South and Northeast, with the most significant effects were observed on the number of persons employed in agricultural establishments family. Instead, PRONAF did not affect the concentration of land ownership and the proportion of small establishments, which indicates the need for specific policies to overcome this structural problem in Brazil.